P207 Does the Nijmegen correlate to the D12 when used as an outcome measure in patients with breathing pattern dysfunction. (2nd December 2011) - Johnston, R; Shaw, F; Gow, A Menzies; Flude, L
Abstract : Introduction: Breathing pattern dysfunction (BPD) in patients with and without respiratory disease is linked to disproportionate dyspnoea. Asthma patients in particular have a high prevalence of BPD. The Nijmegen questionnaire (NQ) is a validated outcome measure in patients with no underlying respiratory pathophysiology, not in patients with organic disease. There is no validated tool that can be used to assess the effectiveness of breathing retraining in patients with BPD. The Dyspnoea-12 (D12) questionnaire provides a global score of breathlessness severity and is validated in respiratory disease, but not in patients with BPD. The aim was to correlate the D12 to the NQ and assess its use as an outcome measure for patients with BPD. Pre and post scores were compared to assess the effectiveness of Physiotherapy breathing retraining on patients with BPD referred to our tertiary centre. Method: We included all Physiotherapy referrals to the outpatient department of the Royal Brompton Hospital for BPD between January and July 2011. The D12 and NQ were completed before and after 3 Physiotherapy interventions and respiratory rate was also measured. Results: Initial data were available for 26 patients: mean (SD) age 47.6 yrs (13), 16 (62%) female, 13 (50%) had a diagnosis of asthma. Post intervention data were available for 17 (65%) patients. Respiratory rate did not correlate with the NQ or D12 in any of the groups. There was a statistically significant correlation between the NQ and D12 both pre (p=0.0017, R=0.59) and post (p=0.0156, R=0.58) intervention. A statistically significant difference pre and post intervention was shown in the NQ (p=0.0242 mean (SD)=7.35 (12.1)) and the D12 (p=0.0127). Conclusion: The data suggests that breathing retraining provides both a clinically effective and statistically significant improvement in symptoms of patients with BPD. There was a significant correlation between the D12 and NQ scores in patients referred with BPD. This highlights that the D12 may be an appropriate outcome measure in this patient population.